Electrochemical Biochip Assays Based on Anti-idiotypic Antibodies for Rapid and Automated On-Site Detection of Low Molecular Weight Toxins - Schulz, Katharina; Pöhlmann, Christopher; Dietrich, Richard; Märtlbauer, Erwin; Elßner, Thomas (Frontiers in Chemistry, 2019)
Phycotoxins and mycotoxins, such as paralytic shellfish poisoning toxins, type A trichothecenes, and aflatoxins are among the most toxic low molecular weight toxins associated with human poisoning incidents through the consumption of naturally contaminated food. Therefore, there is an utmost need for rapid and sensitive on-site detection systems. Herein, an electrochemical biochip for fast detection of saxitoxin, T-2 toxin and HT-2 toxin as well as aflatoxin M1 using a portable and fully automated detection platform (pBDi, portable BioDetector integrated) was developed. Toxin analysis is facilitated upon the biochip via an indirect competitive immunoassay using toxin-specific antibodies combined with anti-idiotypic antibodies. The developed biochips enable detection in the low ng/mL-range within 17 min. Moreover, the assays cover a wide linear working range of two to three orders of magnitude above the limit of detection with an inter-chip coefficient of variation lower than 15%. A broad specificity to a large number of congeners within the respective toxin group allows efficient screening of contaminated samples for the presence of these low molecular weight toxins. Moreover, the established biochips are applicable to detect saxitoxin, HT-2 toxin and aflatoxin M1 in human urine as biomarkers of acute exposure. Thus, the developed biochip assays can be used to rapidly and reliably identify severe intoxications caused by low molecular weight toxins.